Performance Evaluation of DCT, FFT and DWT Basis Compressive Sensing for Guided Wave Ultrasonic Testing - Mohd Nadzri, Muhamad Muzakkir; Ahmad, Afandi (International Journal of Integrated Engineering, 2024)
Guided wave ultrasonic testing (GWUT) is among the optimum method that has been broadly utilised for structural health monitoring (SHM) applications. With the rapid development of wireless and real-time in SHM fields, the implementation of compressive sensing (CS) for GWUT has received attention for better signal-processing compression techniques. Instead of the traditional compression method, an efficient CS promises a compression method that can sample signals lower than the Nyquist sampling rate. In CS, the signal basis is an important parameter to be investigated that will influence the compression performance. This study transforms the GWUT input signal into three (3) types of familiar signal basis, such as discrete cosine transform (DCT), fast Fourier transform (FFT) and discrete wavelet transform (DWT), and the compression performance using the CS method is examined and compared. The results reveal that among these three (3) signals basis, considered the trade-off between quality and compressed performance, the DCT is the best basis and the sparsest transform signal for GWUT with excellent compressed ability and quality of reconstruction. 50 to 80 percent of the M/N sampling ratio was recorded as the best sampling ratio for DCT, with SNR values ranging from 37 dB to 44 dB.